The Influence of Brand Image and Trust on Purchase Decisions in TikTok Shop - Kathrine Syam Wijaya (Journal Research of Social Science, Economics, and Management, 2023)
The present study aims to investigate the relationship between brand image, trust, and purchase decisions in the context of the TikTok Shop. As the e-commerce industry continues to evolve, factors influencing consumer purchase decisions have become increasingly complex. This research focuses on the impact of brand image and trust on consumers' decisions to make purchases within the TikTok Shop platform. In this study, a quantitative research approach is adopted, utilizing survey questionnaires to collect data from a sample of TikTok Shop users. The questionnaires assess participants' perceptions of brand image, trustworthiness, and their purchase intentions within the TikTok Shop environment. Statistical analyses, including correlation and regression analyses, are employed to examine the relationships between these variables. The findings of this study contribute to the understanding of how brand image and trust play pivotal roles in shaping consumers' purchase decisions within the context of the TikTok Shop. By shedding light on the factors that influence consumers in making online purchases, businesses and marketers can develop strategies to enhance their brand image and foster trust among consumers. This, in turn, can lead to increased purchase intentions and ultimately drive business growth. This research provides valuable insights for marketers, practitioners, and researchers seeking to optimize their marketing efforts within the dynamic and competitive e-commerce landscape. Understanding the interplay between brand image, trust, and purchase decisions in the context of TikTok Shop can guide businesses in developing effective marketing campaigns and building stronger relationships with their target audience.